An analysis of teacher’s multilingual practices used in teaching EFL students - Muthalib, Kismullah Abdul; Ummah, Sari Yatul; Silviyanti, Tgk Maya (Universitas Islam Negeri Banda Aceh, 2024)
The aim of this study was to analyze the multilingual practices and predominant languages used by an English teacher during classroom activities. It also sought to assess students' reactions to the teacher's language use and to determine the rationale for the teacher's choice of each language in the English language classroom. Six observations were conducted in the three selected classes to assess the use of Indonesian, English, Kluet, Jamee and Acehnese in classroom activities. A total of 48 student respondents from three classes completed the questionnaires, with the English teacher at Junior High School 1 Kluet Timur serving as the sample. The results showed that Indonesian was the most dominant language used in the classroom with a rate of 47.1%, followed by English, Kluet Jamee and Acehnese. The responses to the questionnaire showed that the students believed that using Indonesian and local languages in learning English could help them to understand the material presented by the teacher. In addition, the study showed that the teacher's reason for using Indonesian and local languages was to enhance students’ comprehension of English materials, which ensure effective learning.